2017
DOI: 10.1177/1758573217700839
|View full text |Cite
|
Sign up to set email alerts
|

Managing acromio-clavicular joint pain: a scoping review

Abstract: High-level studies on treatment modalities for acromioclavicular joint pain are limited. As such, there remains little evidence to support one intervention or treatment over another, making it difficult to develop any evidenced-based patient pathways of care for this condition.Level of evidence: 2A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…No studies have been identified that compared the effectiveness of nonpharmacological interventions versus surgical interventions in individuals with persistent ACJ osteoarthritis. 8,49 The current evidence for surgical intervention as a treatment option for persistent ACJ osteoarthritis has been derived from studies comparing the efficacy of a single surgical technique or the effectiveness of different surgical techniques. 8,14,55 Recently the role of surgical management for rotator cuff tears and subacromial impingement syndrome has been challenged.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No studies have been identified that compared the effectiveness of nonpharmacological interventions versus surgical interventions in individuals with persistent ACJ osteoarthritis. 8,49 The current evidence for surgical intervention as a treatment option for persistent ACJ osteoarthritis has been derived from studies comparing the efficacy of a single surgical technique or the effectiveness of different surgical techniques. 8,14,55 Recently the role of surgical management for rotator cuff tears and subacromial impingement syndrome has been challenged.…”
Section: Resultsmentioning
confidence: 99%
“…This recommendation is in line with a recent scoping review that critically evaluated the efficacy of conservative and surgical treatments for adults with ACJ pain. 49 Clearer diagnostic criteria for persistent ACJ osteoarthritis need to be developed so that individuals with isolated clinical presentations can be ascertained and tailored interventions for this clinical population be developed. For the effectiveness of nonpharmacological interventions to be meaningfully compared, it is imperative that future studies use outcome measures validated for ACJ osteoarthritis.…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…Some predictive clinical factors found in multivariable regression analysis are local tenderness to palpation, female sex and dominant shoulder 38 and when comparing MRI findings of symptomatic and asymptomatic patients, bone marrow oedema was found only in symptomatic shoulders 256 . Both lateral clavicle resection (open and arthroscopic) and corticosteroid injection can relieve symptoms, but directly comparative studies are lacking 42 .…”
Section: Procedures Adjunctive To Repairmentioning
confidence: 99%
“…The few studies dealing with the medical management of the disease conducted no comparative assessment of drug therapies, physiotherapy, joint manipulation or corticosteroid injections. 5 The Visual Analogue Scale (VAS) to measure pain at rest, pressure pain and night-time…”
Section: Introductionmentioning
confidence: 99%
“… 4 An X-ray of the centre of the AC joint should then be taken to confirm degenerative joint disease. In their literature review, Chaudhury 5 report that it is difficult to conduct a comparative evaluation of the various medical and non-medical treatment strategies for AC joint pain because these strategies cannot be compared in a blinded fashion. The few studies dealing with the medical management of the disease conducted no comparative assessment of drug therapies, physiotherapy, joint manipulation or corticosteroid injections.…”
Section: Introductionmentioning
confidence: 99%